Intensity of Supervision of The Head of Madrasah and Teacher Performance on The Achievement of Learning Islam In Tsanawiyah Madrasah - Subaidi Subaidi; Khoirul Ulum (At-Tarbiyat, 2021)
This research is to find out school principal supervision intensity to Islamic education lesson achievements at MTs Wedung Demak; teachers’ performance to Islamic education lesson achievements at MTs Wedung Demak; school principal supervision intensity and teachers’ performance to Islamic education lesson achievements at MTs Wedung Demak. The population of this research is teachers of Islamic education lesson achievements. The sampling technique used is total sampling, which means that all the population is used as a sample. The data is collected by using questionnaires and documentation. The data analysis uses percentage description and multiple linear regressions. The results of this research is: 1) School principal supervision intensity (x1) acquired t count = 8,234 with significance t = 0,000 and t count > t table (8,234> 2,021) or significance t is smaller than 0,05 (0,000 < 0,05), so there is the influence of the school principal supervision intensity to Islamic education lesson achievement; 2) teachers’ performance (x2) obtained t count of 3,314 with t significance of 0,002 and t count > t table ( 3,314 > 2,000 ) or significance would 0,05 ( 0,002 > 0,05 ), so there is influence on teacher performance to Islamic education lesson achievements; 3) School principal supervision intensity (x1) together with teacher performance (x2) f value count of 45,713 with significantly by 0,000 < 0,05 and f count > f table ( 45,713 > 3,204 ), influence school principal supervision intensity and teacher performance together Islamic education lesson achievements MTs Wedung Demak.